Relationship between Firm Readiness and the Adoption of Digitalized Marketing Operations Tactics by Chain Supermarkets in Kenya - Tatua, Joseph; Mwenda, Lilian; Wachira, Anita (International Journal of Strategic Marketing Practice, 2023)
Purpose: Digitalized marketing operations has transformed the retail sectors by providing access to instantaneous, inexpensive contact among sellers, buyers, investors and advertisers anywhere in the world. This has made traditional marketing and sales strategies less effective in today's markets. However, a digital divide exists between consumers and retailers with many retailers failing to leverage the potential of or meet the digital expectations of their customers. This gap between consumers' expectations and retail offerings puts at risk more than just shopping revenue that physical store could have earned online. It also poses a serious threat to overall revenue and challenges how they respond to and anticipate customers' shopping habits in-store. There are different drivers of adopting digitalized marketing operations tactics, including firm size, firm readiness, perceived benefits, perceived barriers, customer pressure and competitive pressure. This study addressed the relationship between firm readiness and the adoption of digitalized marketing operations tactics by chain supermarkets in Kenya. Methodology: The research study considered the positivism research philosophy and adopted a descriptive research design. The study's target population was 180 retail chain supermarket stores in Kenya and all the 180 retail chain supermarkets were included in the sample. The research instrument of the study was a semi-structured questionnaire administered to all the 180 chief operations managers by use of google surveys and/or drop and pick method. The quantitative information was analyzed by the help of SPSS program (v.25.0) and Excel. The findings were presented as averages, standard deviations, counts and percentages using tables. Findings: The findings revealed that firm readiness which include technology sufficiency, technology compatibility, human capacity to absorb new technology and top management support (Î²=0.295, p=0.000) have a positive and significant relationship with the adoption of digitalized marketing operations tactics by chain supermarkets in Kenya. This implies that improvement in 1 unit of the aspects related to firm readiness improves the adoption of digitalized marketing operations tactics by chain supermarkets in Kenya by 0.295 units. Unique Contribution to Theory, Practice and Policy: The study bridges the gap between theoretical constructs of digital marketing adoption and their practical application within the chain supermarkets in Kenya, offering valuable perspectives that will drive the sector's growth and competitiveness in the digital age.